Mutagenic and genotoxic effects of the Atrazine herbicide in Oreochromis niloticus (Perciformes, Cichlidae) detected by the micronuclei test and the comet assay - de Campos, Bruna [UNESP]; de Angelis, Ventura Dejanira de Fransceschi [UNESP]; Marin-Morales, Maria Aparecida [UNESP] (Academic Press Inc. Elsevier B.V., 2008)
Atrazine is the triazinic herbicide most found in the rural aquatic environments due to its extensive use and its stability in such places. The mutagenicity and the genotoxicity of different concentrations of the Atrazine herbicide were determinated by the micronucleus test and the comet assay, using Oreochromis niloticus as test-system. The tested concentrations of Atrazine herbicide were 6.25, 12.5 and 25 mu g/L, both for the micronuclei test and for the comet assay. The results showed a significant rate of micronuclei and nuclear abnormalities for all the tested concentrations of Atrazine herbicide. For the comet assay, we also observed results significantly different from the control in 6.25, 12.5 and 25 mu g/L concentrations. Due to these results, we could infer that such herbicide may be dangerous to the lives of those organisms exposed to it. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: Atrazine herbicide; Oreochromis niloticus; micronucleus; nuclear abnormalities; micronuclei test; comet assay; genotoxicity; mutagenicity; DNA fragmentation; triazines